Olivia-- and the missing toy - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2003)
When her best toy mysteriously disappears, Olivia the feisty pig is determined to find out who is responsible.
Booklist starred
School Library Journal
Wilson's Children
2.3
K-3.
K-3
Keywords: Lost articles -- Juvenile fiction; Swine -- Juvenile fiction; Toys -- Juvenile fiction; Lost and found possessions -- Fiction; Pigs -- Fiction; Toys -- Fiction; Lost and found possessions -- Fiction; Pigs -- Fiction; Toys -- Fiction